Effects of octreotide acetate and amniotic membrane on wound healing in experimental glaucoma surgery - Demir, T; Turgut, B; Celiker, U; Ozercan, I; Ulas, F; Akyol, N (Springer, 2003)
Wound healing affects the success of glaucoma filtering surgery. Antimetabolites and antifibrotic agents are used in the modulation of surgical trauma. This study is performed to evaluate the effects of amniotic membrane and octreotide acetate on wound healing. Thirty pigmented rabbits were divided into three groups each including 10 animals. Trabeculectomy and topical postoperative prednisolone sodium phosphate four times daily for 7 days were applied to one eye of all the rabbits. After trabeculectomy, octreotide 10 mug three times daily applied topically to the octreotide group for 14 days and amniotic membrane transplantation was performed by suturing amniotic membrane between scleral flap and sclera to the amniotic membrane group. The operated eyes of the rabbits were enucleated on the 14th day of the operation and histopathological specimens were obtained from the bleb sites and they were evaluated by light microscope. Fibroblast and macrophage number per cm(2) were counted and the average values were calculated. Compared with the control group, the fibroblasts and macrophages significantly decreased in the other two groups (p < 0.0001, p < 0.0001, respectively). The mean number of fibroblasts was lower than those of the control and amniotic membrane groups (p < 0.0001, p < 0.0001, respectively). Similarly the mean macrophage number was significantly lower in the octreotide group versus the control and amniotic membrane groups (p < 0.0001, p < 0.01, respectively). Octreotide administration and amniotic membrane transplantation might be alternative treatments in modulating the wound healing after trabeculectomy.
Keywords: trabeculectomy; wound healing; octreotide; amniotic membrane